Levels and trends in the income mobility of U.S. families, 1977 - 2012 - Katharine L. Bradbury (Federal Reserve Bank of Boston, 2016)
Much of America's promise is predicated on economic mobility - the possibility that people can move up and down the economic ladder during their lifetimes. Mobility is of particular consequence when economic disparities are increasing. Using panel data and mobility concepts and measures adapted from the literature, this paper examines 10-year income mobility levels and trends for U.S. working-age families during the time span 1977 - 2012. According to many measures, mobility, already limited in the 1978 - 1988 decade, declined over ensuing decades: families' later-year incomes increasingly depended on their starting place, and the distribution of longer-term family incomes became less equal.
Keywords: D31; D63; I32; J15; 330; Income mobility; income inequality; income distribution